QTL‐seq for rapid identification of candidate genes for 100‐seed weight and root/total plant dry weight ratio under rainfed conditions in chickpea. Issue 11 (26th May 2016) - Singh, Vikas K.; Khan, Aamir W.; Jaganathan, Deepa; Thudi, Mahendar; Roorkiwal, Manish; Takagi, Hiroki; Garg, Vanika; Kumar, Vinay; Chitikineni, Annapurna; Gaur, Pooran M.; Sutton, Tim; Terauchi, Ryohei; et al.
Summary: Terminal drought is a major constraint to chickpea productivity. Two component traits responsible for reduction in yield under drought stress include reduction in seeds size and root length/root density. QTL‐seq approach, therefore, was used to identify candidate genomic regions for 100‐seed weight (100SDW) and total dry root weight to total plant dry weight ratio (RTR) under rainfed conditions. Genomewide SNP profiling of extreme phenotypic bulks from the ICC 4958 × ICC 1882 population identified two significant genomic regions, one on CaLG01 (1.08 Mb) and another on CaLG04 (2.7 Mb) linkage groups for 100SDW. Similarly, one significant genomic region on CaLG04 (1.10 Mb) was identified for RTR. Comprehensive analysis revealed four and five putative candidate genes associated with 100SDW and RTR, respectively. Subsequently, two genes ( Ca_04364 and Ca_04607 ) for 100SDW and one gene ( Ca_04586 ) for RTR were validated using CAPS/dCAPS markers. Identified candidate genomic regions and genes may be useful for molecular breeding for chickpea improvement.